Structural peculiarities of rats’ testes development after introduction of female hormones during pregnancy - Hryhorieva, O. A.; Topolenko, T. A.; Kovalchuk, K. S.; Guminskiy, Y.; Matveishyna, T. M.; Grinivetska, N. V.; Lazaryk, O. L.; Григор'єва, Олена Анатоліївна; Тополенко, Тетяна Анатоліївна; Ковальчук, Катерина Сергіївна; Матвєйшина, Тетяна Миколаївна; Грінівецька, Наталія Валеріївна; et al. (My University, 2023)
The aim: To de!ne regularities of testicular construction of the rats’ o"spring at 1-90 days of postnatal life after the introduction of female sex hormones to pregnant rats during the second and third periods of pregnancy Materials and methods: The study was conducted on the testes of white laboratory rats’ o"spring during three months of life. Pregnant rats were exposed to intravaginal injection of Utrozhestan during the second and third periods of pregnancy. histological methods were used. Analysis of the obtained results was conducted by means of statistical methods with the use of computer license program «Statistica for Windows 13» (StatSoft Inc., # JPZ804I382130ARCN10-J). Results: Administration of female sex hormones to pregnant female rats leads to a reducing of the relative area, occupied by the convoluted seminiferous tubules with lumen, and increasing in relative area, occupied by extracellular matrix, starting from the 30th and up to the 90th observation day in the o"springs’ testes. During the third month after birth, in experimental group a decreasing of the testicles’ spermatids di"erentiation degree is determined Conclusions: During the study, the following results and conclusions were obtained: decreasing of the relative area, occupied by convoluted seminiferous tubules, increasing in relative area, occupied by extracellular matrix, also decreasing Leydig cells relative amount and a delaying of spermatid di"erentiation process after exposing to female sex hormones during pregnancy, especially during third period, can lead to disruption of spermatogenesis and spermiogenesis in the future.
O. A. Hryhorieva - ORCID: 0000-0002-6101-8322; T. A. Topolenko - ORCID: 0000-0001-7832-7941; K. S. Kovalchuk - ORCID: 0000-0002-4920-0615; T. M. Matveishyna - ORCID: 0000-0002-9078-9580; N. V. Grinivetska - ORCID: 0000-0001-9642-0285; O. L. Lazaryk - ORCID: 0000-0003-1937-1226.
Keywords: testes; female sex hormones; Utrozhestan; Leydig cells; spermatids